2014
DOI: 10.1016/j.jphotobiol.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid diosmetin increases ATP levels in kidney cells and relieves ATP depleting effect of ochratoxin A

Abstract: a b s t r a c tDiosmetin (DIOS) is a flavone aglycone commonly occurring in citrus species and olive leaves, in addition it is one of the active ingredients of some medications. Based on both in vitro and in vivo studies several beneficial effects are attributed to DIOS but the biochemical background of its action seems to be complex and it has not been completely explored yet. Previous investigations suggest that most of the flavonoid aglycones have negative effect on ATP synthesis in a dose dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 50 publications
(82 reference statements)
0
26
0
1
Order By: Relevance
“…These isomers have been shown to exhibit common biological effects, such as osteoporosis prevention [5]. Diosmetin is an active ingredient of some medications [6] and has been reported to display several biological properties, including anticancer effects [7,8] and antibacterial actions [9] - . Similar to diosmetin, chrysoeriol is mainly distributed in many plant products, such as parsley [10] and peanut hull [11].…”
Section: Introductionmentioning
confidence: 99%
“…These isomers have been shown to exhibit common biological effects, such as osteoporosis prevention [5]. Diosmetin is an active ingredient of some medications [6] and has been reported to display several biological properties, including anticancer effects [7,8] and antibacterial actions [9] - . Similar to diosmetin, chrysoeriol is mainly distributed in many plant products, such as parsley [10] and peanut hull [11].…”
Section: Introductionmentioning
confidence: 99%
“…These three fractions have different chemical characteristics. A previous study showed that pinocembrin and galangin inhibit ATPase activity, although apigenin cannot or can but only slightly [19].…”
Section: Discussionmentioning
confidence: 95%
“…44 Diosmetin is one of the main active ingredients of some medications. 45 The metabolite acacetin can exert anti-inflammatory, anticancer, and antihypertension activities. 46,47 Deglycosylation is an important step in the absorption and metabolism of glycosides.…”
Section: ■ Discussionmentioning
confidence: 99%